Developing Vocabulary Materials for Teaching Learning Process - Fitriah Fitriah (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2020)
Language instruction has five important components that they are students, a teacher, materials, teaching methods and evaluation. Teaching materials should help the students to learn or as a part of the class activities of instruction learning in the class. The materials should help the teacher and the students. Ideally, teaching materials will be tailored to the content in which they are being used, to the students in whose class they are being used, and the teacher. Teaching materials come in many shapes and sizes, but they all in common the ability to support students learning. So, teaching materials can support students learning and increase students’ success. Hence, instructional materials for effective teaching. The quality of those materials is a valuable skill that the teacher must be mastered. The materials chosen in teaching learning include textbook that extent to which a curriculum that will involve teacher made material, which content of additional activities and exercises, handouts, charts, review sheets, etc.